State Power Balance In Governing Land: Law And Regulation Of Vietnam - NGA, Pham Thanh (Indonesia Strategic Sustainability, 2022)
Recent years have seen an increase in the number of cases involving illegal land purchases in Vietnam. In addition to making people lose faith in the Party's and the State's leadership, it also reduces the confidence of both domestic and foreign investors and businesspeople engaged in land leasing and commercial development in Vietnam. Land is the most important natural resource of each country worldwide. When used effectively, the state maintains a stable political system and achieves economic sustainability. However, countries' authorities still face many challenges when governing land resources. Although there have been many efforts to enact Laws and regulations to improve the legal system on land, Vietnam's authority administration is still very complicatied now. Vietnam's National Assembly is collecting opinions from relevant organizations and individuals to finalize the draft and prepare to promulgate the revised 2022 Law of Land. In this article, the author clarifies the issue of state power control when expropriating land in Vietnam. From there, the author suggests ways to strengthen the legal framework for land when revising and creating new laws and regulations for the land, balancing the interests of the government and the people of Vietnam for the coming period. To do this research, the author combines many kinds of methodologies, such as surveying to collect data and opinions of experts, people and authorities, analyzing the laws and regulations related to managing land.